2015
DOI: 10.1364/josaa.32.001643
|View full text |Cite
|
Sign up to set email alerts
|

Infrared and visible image fusion with spectral graph wavelet transform

Abstract: Infrared and visible image fusion technique is a popular topic in image analysis because it can integrate complementary information and obtain reliable and accurate description of scenes. Multiscale transform theory as a signal representation method is widely used in image fusion. In this paper, a novel infrared and visible image fusion method is proposed based on spectral graph wavelet transform (SGWT) and bilateral filter. The main novelty of this study is that SGWT is used for image fusion. On the one hand,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(9 citation statements)
references
References 29 publications
0
9
0
Order By: Relevance
“…The final fused images are obtained by inverse transforms. There are several representative transforms for infrared and visible image fusion: pyramid transforms [28][29][30], wavelet transforms [31][32][33], contourlet transforms, and non-subsampled contourlet transform [12,34,35]. SR [36] is a novel image representation theory that simulates the sparse coding mechanism of human vision systems [37].…”
Section: Conventional Fusion Methodsmentioning
confidence: 99%
“…The final fused images are obtained by inverse transforms. There are several representative transforms for infrared and visible image fusion: pyramid transforms [28][29][30], wavelet transforms [31][32][33], contourlet transforms, and non-subsampled contourlet transform [12,34,35]. SR [36] is a novel image representation theory that simulates the sparse coding mechanism of human vision systems [37].…”
Section: Conventional Fusion Methodsmentioning
confidence: 99%
“…It is also observed that the difference in performance between the proposed frame and the spectrum-adapted frame is more pronounced when using up to eight scales. In recent studies that use the SGWT [31], [51]- [55], typically, up to six scales are used, which can be explained by observing that the performance for this frame saturates at J = 5. In contrast, the proposed frames show a monotonic increase in performance also for larger number of scales.…”
Section: Signal Denoisingmentioning
confidence: 99%
“…Mean and standard deviation: The statistical parameters mean (μ), a measure of average intensity and variance ( (9) where MN is the total number of pixels in the image and x ij is the pixel intensity at that location.…”
Section: Performance Evaluation 41 Subjective and Objective Evaluationmentioning
confidence: 99%
“…Several fusion methods for low-light visible and infrared image fusion have been proposed by researchers [7][8][9] . Generally, pixel-based fusion methods are employed for fusion as they are simple to implement as compared with the computational complexity in implementing region-based and feature-based fusion techniques.…”
Section: Introductionmentioning
confidence: 99%